THE USE OF VISUAL AIDS IN TEACHING ENGLISH GRAMMAR TO YOUNG LEARNERS: A CASE STUDY IN A PRIMARY SCHOOL = VIỆC SỬ DỤNG GIÁO CỤ TRỰC QUAN TRONG GIẢNG DẠY NGỮ PHÁP CHO HỌC SINH: NGHIÊN CỨU TẠI MỘT TRƯỜNG TIỂU HỌC - Nguyễn, Thị Thanh Hòa (2020)
The use of visual tools in teaching and learning is considered by many researchers, but there is a lack of study on the use of these tool in teaching grammar at primary level. The study aims at finding some types of visual aids implemented in class and their used frequencies, the strengths and weaknesses of them and the satisfaction level of teachers when using these tools. Mixed research, which is the combination of qualitative research and quantitative one, was implemented with the population was three official teachers at Pham Hong Thai Primary school. The analysis of the result revealed that chalkboards were utilized the most as they were equipped in every class and the preparation for the lesson instructed by blackboard was the least among these six tools. Besides, in spite of the advantages that projectors bring along, this tool was less used as it took time to prepare. The most used visual aids at this school were pictures and flashcards because of its availability. Last but not least, the satisfaction level of the teachers was based on the strengths and weaknesses of these tools instead of their used frequencies in class. The recommendations, then, can facilitate grammatical teaching and learning process with the taking advantages of visual aids in classroom activities.